A aldravia e o hiperlink na construção de identidades literárias - Luciana Amaro (2021)
This dissertation presents a proposal of a sequence of activities based on the genre didactic project of Guimarães and Kersch (2012) combined with the basic sequence of literary literacy (Cosson, 2009). The subjects of study are the reading and writing of “aldravias” – a poetry genre that emerged in the city of Mariana (MG) -, and also its contribution to the formation of literary identities. The activities promote literary experiences to enlarge the knowledge around the “aldravia” movement, the appropriation of its history, and the expansion of the theoretical knowledge about poetry. Furthermore, poetic writing production using the hyperlink is encouraged, creating a network of texts connected by semantic approaches, enabling diverse readings. Therefore, the accomplishment of a digital book that embraces the “hyperlinktic” character of “aldravias” is made possible. The research has a qualitative character and, by being propositive, it can be developed with elementary school students to consolidate the literary literacy. Through this research, the constant need to rethink pedagogical practices is verified, in order to fulfill the demands and reach the contexts that are in a constant process of reinvention.